Silent hill 2 and the curious case of invisible agency - Şengün, S. (My University, 2013)
This paper outlines the concept of agency in interactive narratives and focuses on the video game Silent Hill 2 as a successful example that defies the very concept. In what ways agency was deemed as an essential part in interactive narratives and narrative video games are summarized. Then the method of agency in Silent Hill 2 is proposed as an alternative to our familiar understanding of the concept agency and is entitled as invisible agency. © Springer International Publishing 2013.
6th International Conference for Interactive Storytelling, ICIDS 2013 -- 6 November 2013 through 9 November 2013 -- Istanbul -- 102540
Keywords: Agency; Autonomy; Interactive Narrative; Invisible Agency; Narrative Video Game; Silent Hill; Video Game; Video Game Experience; Agency; Autonomy; Interactive Narrative; Invisible Agency; Silent Hill; Video Game; Artificial İntelligence; Computer Science; Computers; Interactive Computer Graphics